Assessment of the red blood cell proteome in a dog with unexplained hemolytic anemia. (19th July 2018) - Black, Victoria L.; Heesom, Kate; Whittington, Fran; Davis, Sean; Tasker, Séverine; Adamantos, Sophie; Davidson, Andrew D.
Abstract: A 7‐year‐old female neutered Jack Russell Terrier was presented to Langford Vets, the University of Bristol, with a history of chronic intermittent lethargy. Investigations and clinical course were compatible with hereditary hemolysis due to a red blood cell membrane defect. Proteomics was used to explore protein alterations in the presence of a hypothesized red blood cell membrane protein deficiency. Proteomic analysis revealed downregulation of the band 3, and alpha‐ and beta‐adducin proteins, and alterations in the red blood cell proteome consistent with previous reports of changes due to the presence of reticulocytosis and ongoing hemolysis. The spectrum of protein alterations identified in the affected dog may be homologous to a band 3 protein deficiency secondary to hereditary spherocytosis, as described in people.